Cause investigation of large deformation of a deep excavation support system subjected to unsymmetrical surface loading. (January 2020) - Ou, Xuefeng; Zhang, Xuemin; Fu, Jinyang; Zhang, Cong; Zhou, Xianshun; Feng, Han
Highlights: Deflection modes of support system in deep excavation subjected to unsymmetrical surface loading is investigated. The principal causes of rotation behavior of the support system are clarified. The stiffness of subsoil has much influence on the deformation of support system. The design optimization method for the large deformation controlling is proposed. Abstract: This paper presents a case study to investigate the large deformation of a deep excavation supporting system closed to a railway with high embankment. The in-situ monitoring is used to determine the effects of the unsymmetrical surface loading on the support system. Meanwhile, the optimization of its design schemes is discussed by the finite element method (FEM). The monitoring results present the support system rotates away from the railway side during the excavation process. The deflection of the diaphragm walls significant affects the railway settlement especially when the maximum movement of lateral wall exceeds 21 mm. The observed maximum lateral deflection exceeded 50.9 mm, which caused considerable settlement (106.0 mm) to the nearby railway. The results of the FEM indicate that soil strengthening inside the deep excavation is an optimized scheme. It can reduce 35.8% maximum wall deflection on bias loading side so that largely control the rotate deformation of the support system, and the scheme may also reduce about 70% maximum settlement of the railway bed.